Autorytet świętego Augustyna w Marcina Kromera dyskusji z Reformacją - Dziuba, Agnieszka (Vox Patrum, 2025)
Marcin Kromer was one of the first Polish humanists who actively joined the fight against the Reformation. In Polish conversations and in their Latin, much more extensive version, he not only undertook to refute the theological arguments of Martin Luther and his followers, but above all, he gave a competent exposition of the teachings of the Catholic Church at that time. He had an excellent knowledge of the text of the Holy Scripture along with its commentaries, was well-read in the writings of the Fathers of the Church and theologians of later eras up to contemporary times, and was also well versed in the books of his adversaries. Kromer’s erudition allowed him to create, especially in the Latin Conversations, the image of a priest (Monachus) who courageously and without hesitation refutes the arguments of his opponents and clearly explains the intricacies of Catholic theology. Among the authorities whose writings and views Kromer most often refers to is Augustine, a writer extremely important to Luther himself. The author of the dialogue uses the figure of the bishop of Hippo in various ways. Sometimes his name appears among others writing on a given topic, sometimes he is a "time marker". Most often, however, his writings provide arguments in the discussion on the understanding and interpretation of the Holy Scripture, on the sacrament of baptism, and above all, quotations from his works appear when talking about the Tradition of the Church, councils and hierarchy in the Church. Kromer’s appreciation of Augustyn is demonstrated by the fact that he independently translates some of his thoughts into Polish. In this way, Polish society, which does not know Latin, comes into contact with the words of an African bishop for the first time. It is also important that Kromer noticed and appreciated Augustine’s style. The Polish writer sometimes uses successful phrases from the works of the Bishop of Hippo to decorate and enrich his own sentences with elocution. It can therefore be said that Augustine’s visible authority in Kromer’s dialogues is used by the humanist in a diverse and erudite way.